NumPy 1.5 beginner's guide : an action-packed guide for the easy-to-use, high performance, Python based free open source NumPy mathematical library using real-world examples /: an action-packed guide for the easy-to-use, high performance, Python based free open source NumPy mathematical library using real-world examples. (2011) - Unknown
No abstract available